Polymer-Gel Radiation Dosimetry of Laser-Based Relativistic Electron Sources for Biomedical Applications: First Qualitative Results and Experimental Challenges - Fitilis, Ioannis; Grigoriadis, Anastasios; Tazes, Ioannis; Petrakis, Stelios; Andrianaki, Georgia; Dimitriou, Vasilios; Bakarezos, Efthimios; Benis, Emmanouil P.; Tsiapa, Irini; Boursianis, Themistoklis; Kalaitzakis, Georgios; Bontzos, Georgios; et al. (Frontiers in Physics, 2022)
The generation of laser based relativistic electron sources involves impressive basic science as well as innovative applications. This study reports first novel qualitative results on polymer-gel radiation dosimetry of ultrafast laser-based relativistic electron beams. The fabricated polymer-gels are irradiated by the ultra-high dose rate (FLASH) laser-generated electron beams and then are analysed using magnetic resonance imaging. The reading of the irradiated dosimeters is performed using a clinical 1.5 Tesla Magnetic Resonance Imaging system. Three-dimensional colour parametric T2 maps are then constructed from the original PD-T2 weighted images obtained from the clinical MRI scanner. For comparison, the gels are also irradiated with standard electron beams of various energies utilizing a radiotherapy clinical linear accelerator system. For the calibration measurements of the gel dosimetry method, special calibrated dosimetric films are also implemented. The preliminary results demonstrate the potential of polymer gel dosimetry for 3D-dose-distribution of FLASH type irradiation of laser generated electron beams. Furthermore, they illustrate potential issues related to the polymer gel based dosimetry in challenging irradiation arrangements, such as the oxygen sensitivity and necessity for oxygen impermeable container material.